Improving Corn Production in Southeast Kansas - Gretchen Sassenrath; D. E. Shoup; X. Lin; J. Coltrain; J. Geren; D. Helwig (Kansas Agricultural Experiment Station Research Reports, 2016)
Corn performance and yield varies as a function of the growing environment and soil properties. Components contributing to yield in corn were examined through on-farm measurements of soil properties in southeast Kansas. Environmental variability between the 2013, 2014, and 2015 growing seasons contributed to changes in yield. Management can also impact the amount of harvested yield.
Keywords: corn